2017
DOI: 10.3389/fncel.2017.00085
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Channel C-Terminal and Synaptic Vesicle Tethering: Analysis by Immuno-Nanogold Localization

Abstract: At chemical synapses the incoming action potential triggers the influx of Ca2+ through voltage-sensitive calcium channels (CaVs, typically CaV2.1 and 2.2) and the ions binds to sensors associated with docked, transmitter filled synaptic vesicles (SVs), triggering their fusion and discharge. The CaVs and docked SVs are located within the active zone (AZ) region of the synapse which faces a corresponding neurotransmitter receptor-rich region on the post-synaptic cell. Evidence that the fusion of a SV can be gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Still, neither protein can fully account for tether formation at the membrane. A recent study could show in chicken synaptosomal preparations that the C‐term of Ca V 2.1 and 2.2 Ca 2+ channels might directly tether SVs to the membrane . However, whether the Ca V 1.2 Ca 2+ channel could also fulfill this function has not been tested so far.…”
Section: Discussionmentioning
confidence: 99%
“…Still, neither protein can fully account for tether formation at the membrane. A recent study could show in chicken synaptosomal preparations that the C‐term of Ca V 2.1 and 2.2 Ca 2+ channels might directly tether SVs to the membrane . However, whether the Ca V 1.2 Ca 2+ channel could also fulfill this function has not been tested so far.…”
Section: Discussionmentioning
confidence: 99%
“…Software predictions suggest that the C-terminal exhibits very little predicted secondary structure and its tip could, at least in theory, range far into the surrounding cytoplasm (Wong et al, 2014 ). We recently used nanogold immunocytochemistry to localize the different regions of the CaV2.2 C-terminal within cytoplasm-vacated, but tethered SV-retaining, nerve terminals (Chen et al, 2017 ). We found that the tip of the C-terminal, in the region corresponding to our first identified (C3) SV-binding motif, contacts SVs up to and over 100 nm from the active zone, at least in nerve terminals vacated of cytoplasmic constituents.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides were made with a terminal cysteine to permit conjugation to a carrier protein, KLH (Biomatik, Cambridge, Canada). Immunization of rabbits were done as previously described (Chen et al, 2017 ). All antibodies used in the present study are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common way to tag a protein of interest for EM analysis is immuno-gold labeling [108]. Several studies have impressively shown how antibodies coupled to colloidal gold could be used to identify specific proteins by electron microscopy, e.g., to determine the localization of individual components of NPCs or to investigate the co-localization of neurotransmitters in neurons [89,109,110,111,112,113]. In a proof-of-concept study, native immuno-gold labeling was applied to living cells to identify hRSV assembly sites in mammalian cells and study virus–host interactions [114].…”
Section: Identifying Structures Of Interest Within Cellular Cryo-tmentioning
confidence: 99%